Job Demand-Control-Support Model: A Study of Nigerian Contract Bank Employees: Array - Odetunde, Oladimeji Jamiu (Acta Universitatis Danubius. Œconomica, 2020)
Job Demand-Control-Support (JDCS) model, a theoretical approach applied across Europe and Asia to explain relationship between job factors, occupational health and job outcomes, was applied to the Nigerian work context to investigate the causal relationships of the precarious employment and work conditions of contract bank employees and the negative effects on their work outcome. Cross-sectional design and stratified random sampling were adopted to collect quantitative data from 420 contract bank employees across four banks in Lagos, Nigeria. Hypotheses were tested with SPSS/Process Macro v. 3.5. Findings showed that job demand, job control and social support have significant main causal relationships with job performance of the contract bank employees, with job demands negatively and job control and social support positively relating to their job performance. While social support was found to buffer the negative effect of job demands on their job performance, job control alone and in combination with social support did not show any buffer effect. Study provides partial support for the relevance and applicability of the JD-C-S model in the Nigerian banking work context, particularly with respect to the contract bank employees in the industry. Limitations and implications of study for theory and practice are further discussed.